A combined AHP- and DEA-based approach to measure agility of manufacturing systems. (8th October 2012) - Saleeshya, P.G.; Subash Babu, A.
This paper is related to a real life study carried out in Indian manufacturing organisations to assess the extent to which the agile manufacturing paradigm is recognised and deployed, as this paradigm has been a major objective of many companies. A multi-level framework developed by the authors, along with a questionnaire was used to identify various enabling factors of agility in Indian manufacturing industries. This model helps to determine the measure of agility called 'Effectiveness Index' (EI) at the various hierarchical levels of an organisation. In this paper we propose an approach to measure the agility of manufacturing systems by combining the analytical hierarchy process (AHP) and the data envelopment analysis (DEA) methodologies. The method of AHP was used to identify important agility enablers by deriving appropriate weights (Importance Index). DEA was used to compare and find out the priorities of various units of organisations by making use of the values of EI and Importance Index for agility.